Comparison of clinical outcomes among thrombolyzed and non-thrombolyzed STEMI patients: a single-centre observational study - Kadloor, Parvaiz; Abhishek, G.; Reddy, G. Rajashekhar (International Journal of Research in Medical Sciences, 2022)
Background: There is a paucity of data that compare clinical outcomes, especially morbidity and mortality among thrombolyzed and non-thrombolyzed ST-segment elevation myocardial infarction (STEMI) patients in Indian population. Methods: An observational, single-centre study involving 70 patients who were diagnosed with STEMI from February 2014 to June 2015. Patients were thrombolysed after meticulous evaluation of indications for thrombolytic therapy, and later whenever needed they were subjected to revascularization therapy of either percutenous coronary intervention (PCI) or coronary artery bypass graft (CABG). Then, STEMI patients were categorized into thrombolyzed and non-thrombolyzed groups. Mortality and morbidity parameters such as effort tolerance expressed in terms of New York Heart Association (NYHA) functional class and typical anginal chest pain at 1, 6, and 12-month were primary outcomes. Results: Mean age of the cohort was 53.2 years: 48 men and 22 women. Of the total, 58 (82.9%) patients underwent thrombolysis. Mean window period of thrombolysis therapy was 8.1±2.0 hours. Revascularization was required in 80% of cases. At 12-month, STEMI patients who were thrombolyzed had significantly better effort tolerance in terms of NYHA class than those who were non-thrombolyzed (25% versus 13.8%; p<0.005). At 1 and 6-month, STEMI patients who were thrombolyzed had significantly better effort tolerance in terms of typical anginal pain than those who were non-thrombolyzed (1-month, 82.8% versus 58.3%; p<0.005; 6-month, 4.3% versus 0.0%; p<0.005). Conclusions: This study enlightened the effectiveness of thrombolytic therapy together with revascularization (CABG or PCI) in reducing the morbidity rate than revascularization alone.